(untitled) (MedS Alliance Journal of Medicine and Medical Sciences, 2021)
INTRODUCTION: Wound infection is common across all sex and age groups whichare responsible for significant human mortality and morbidity worldwide.Therefore, the objectives of this study were designed towards isolation and identification of bacteria involved in wound sepsis at Provincial hospital of Madhesh Pradesh, Nepal. MATERIALS AND METHODS: A total of 45 samples were collected from patients of different age groups of both male and female at provincial hospital,Madhesh Pradesh, NepalThe samples were transferred immediately and processed in the microbiology laboratory at Model Multiple College, Janakpurdham. Characterization and identification of the obtained bacteria was based on standard microbiological methods. RESULTS: Out of 45 samples 40 (88.89%) showed bacterial growth. Among the isolates Staphylococcus aureus were present in 15(37.5%), Pseudomonas aureogenosaein 7(17.5%), E.coli in 09(22.50%), and Streptococcus pyogenes in 09 (22.5%) of the total isolated samples. CONCLUSIONS: Staphylococcus aureusin wound infections was found to be dominant.